Production scheduling model in aluminium foundry - Matičević, Gordana (Strojniški vestnik, 2008)
There are numerous methods and strategies for production management which are successfully implemented in the metal industry and in the automobile and machine tools industry in particular. However, little research has been published regarding scheduling foundry operations. Therefore, the main goal ofthis paper is to develop a new mathematical model for scheduling foundry operations based on the MRP II (Manufacturing Resource Planning), JIT (Just inTime) and OPT (Optimized Production Technology) concepts. The research strategy includes a review of available literature and integration of the developed mathematical model into a foundry for testing the model with real data. The proposed model is successfully implemented into the ERP (Enterprise Resource Planning) system of Aluminium Ltd. in Mostar. The conclusions offeredin this paper are based on the results of the tests carried out in thatsingle foundry so that further work is required to validate the findings at other foundries and other manufacturing areas.
Keywords: aluminij; aluminum; proizvodnja; matematični modeli